Games by End-Users: Analyzing Development Environments - Souza, Joana Gabriela Ribeiro de; Prates, Raquel Oliveira (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
Digital games are increasingly present in people's lives, especially in younger people's lives. At times, users want to do more than just play games produced by specialized companies, but would also like to customize them or create and play their own games and share them with their friends. Enabling users with no programming knowledge to develop their games raises several challenges, that range from game design to technical aspects. In this paper, our goal was to investigate the following research question "What strategies and constructs do game engines use to allow users with no previous knowledge of programming to create games?". To do so, we used the Semiotic Inspection Method to analyze two game engines aimed mainly at this audience - GDevelop and Stencyl. As a result, we have identified the main strategies and constructs used in the tools to support game programming by end-users.